Cross-linking of mesoporous bioactive glass nanoparticle incorporated gelatin hydrogels by tannic acid with enhanced mechanical performance and stability - Chen, Si; Li, Meng; Michálek, Martin; Kaňková, Hana; Zhao, Liang; Boccaccini, Aldo R.; Galusek, Dušan; Zheng, Kai (Materialia, 2024)
Gelatin-based hydrogels are used in diverse biomedical applications, such as wound dressings, tissue regeneration, and cell culture models. However, gelatin requires additional cross-linking to form a stable hydrogel. Tannic acid (TA), a polyphenolic compound, can undergo the Michael addition reaction and Schiff's base reaction with primary amine groups in neutral aqueous solutions. In this work, TA was selected as a cross-linker of gelatin to fabricate hydrogels reacting with primary amine groups in the gelatin molecular chain. Primary amine-modified mesoporous bioactive glass nanoparticles (AMBGNs) were added to further enhance the cross-linking of the system. The swelling ratios and weight losses showed that the most stable hydrogels retain approximately 53 % of their mass after 28 days of immersion in PBS solution. Young's modulus increased significantly with the increase in the content of TA and AMBGNs. The addition of TA and AMBGNs also resulted in a substantial reduction of gelation time. The prepared hydrogels possessed adequate stability and mechanical properties and showed potential for customized application in a variety of clinical service settings, such as wound healing, bone regeneration, and soft tissue regeneration.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Bioactive glasses; Gelatin; Tannic acid